Teaching Generation Z: Methodological problems and their possible solutions - Svetlana Popova (Peoples' Friendship University of Russia (RUDN University), 2017)
The focus of the article is on the younger generation of today, which is referred to as Generation Z. The theoretical grounding is based on the Strauss-Howe Generational Theory. The paper discusses lack of motivation to study efficiently and looks into the reasons for misunderstanding which often arises among students and teachers born a few generations earlier. Analysis proves the significance of the difference in values and worldview influenced by various venues, circumstances and surroundings that are unique for each generation. Online games, computerisation, communication via text messages and inability to read the context are mentioned among the features of Generation Z. Difference in the attitude to work and studies is explained with the continuous 'information noise' and special hypertextual perception of reality that influences the personal and social life of Generation Z representatives. The article suggests a number of steps to optimise the teaching process with the coming generation of students.